A spectrum of modes of knowledge sharing between agents - Lomuscio,A; Ryan,M (2000)
The logic S5n is widely used as the logic of knowledge for ideal agents in a multi-agent system. Some extensions of S5n have been proposed for expressing knowledge sharing between the agents, but no systematic exploration of the possibilities has taken place. In this paper we present a spectrum of degrees of knowledge sharing by examining and classifying axioms expressing the sharing. We present completeness results and a diagram showing the relations between some of the principal extensions of S52 and discuss their usefulness. The paper considers the case of a group of two agents of knowledge.